Kontribusi Sosial Pada Masyarakat Melalui Penguatan Kebinekaan Talkshow Modul Nusantara - Wijayanti, Trivena Dyah; Rahardjo, Maria Melita; Listyaningrum, Eunike Milasari; Kurniawan, Mozes; Wijayaningsih, Lanny (LPPM Universitas Palangka Raya, 2024)
Social contribution community service activities are the culmination of a series of Nusantara Module, developed by the community service team, consisting of lecturers of S1 PG PAUD Universitas Kristen Satya Wacana (UKSW) in the Merdeka Belajar Kampus Merdeka (MBKM) program. One of the MBKM programs organized by S1 PG PAUD UKSW in the even semester of 2023/2024 is Pertukaran Mahasiswa Merdeka (PMM). PMM is a student exchange program attended by 10 exchange students from Widya Mandala Catholic University Surabaya who attended lectures at UKSW. The Nusantara Module develops activities to strengthen diversity which are arranged in a series of diversity activities, inspiration activities, reflection activities to social contributions to the community entitled the Nusantara Module Talk Show Series and Social Contributions to the Community. Talk Show Nusantara Module has 3 series, namely: Series 1: “Culture as Identity”; Series 2: “Integrity and Persistence of the Educator” and Series 3: “Challenges and Opportunities of Religious Diversity”. The series ended with social contribution activities to the community, namely Training on Developmental Detection and Socialization of Home Inventory to Parents. Social contribution activities are carried out to 6 (six) families from various religious, ethnic, racial and tribal backgrounds that embody the objectives of the archipelago module. The entire series of activities had a good impact on each participant involved, both exchange students and the community with the level of usefulness shown by the Likert Scale with the results of Good at a percentage of 22.4% and Very Good at a percentage of 77.6%.